Knowledge and Attitude to Biomedical Research of the Post-Graduate Medical Students in Bangladesh - Yasmin, Nelofar; Paul, Shubhra Prakash; Haque, Md Jawadul; Karim, Md Rizwanul; Kumer, Shathi; Kamal, Rawsan; Syem, Md Abu; Ullah, Shah Amanath; Parvin, Most Firoza; Kowsarunnahar, - (TAJ: Journal of Teachers Association, 2022)
Background: Research is the integral part of post-graduation course curriculum. If steps are not taken at an early stage by medical postgraduates who will walk in the path of research in future, the quality of research and its application may be compromised. Students had variable perceptions towards research. The findings of this study could provide insights to improve research training. Objectives: The aim of this study was to assess knowledge and to find out attitude to biomedical research of the post-graduate medical students in Bangladesh. Materials & Methods: This cross-sectional type of descriptive study was carried out in the community Medicine Department of Rajshahi Medical College over a period of 12 months from January to December 2020 among the post-graduate students of different medical colleges. Approval from the Ethical Review Committee (ERC) was obtained prior to the commencement of the study. Purposive sampling technique was used. Pre-designed, validated, structured questionnaire was used to gather information from 325 participants on knowledge and 5-point Likert scale was used for assessment of attitude. Results: In this study excellent knowledge was considered in ≥ 80% correct answers and positive attitude was considered in ≥ 60 score. Out of the 325 study respondents, majority (53.5%) of them were male and pursuing post-graduation in different subjects. Among the respondents, 145 (44.6%) of students had good knowledge, 119 (36.60%) of students had excellent knowledge and 190 (58.5%) had positive attitude toward medical research. Relationship of level of knowledge on biomedical research was not statistically significant for age, sex, religion, marital status, parental and spouse educational status (P>0.05). But association of knowledge was statistically significant for running post-graduation course, type of research involvement and type of medical college of MBBS passing (P < 0.05). Relationship of attitude to biomedical research of the respondents was not statistically significant for age, religion, type of research involvement, type of medical college of MBBS passing, running post-graduation course, marital status, parental and spouse educational status (P>0.05). But male had more positive attitude to biomedical research than female (P<0.05). Conclusion: The study revealed that the respondents had a good knowledge and positive attitude toward biomedical research but they were not able to transform their knowledge and attitude into actual practices. TAJ 2022; 35: No-1: 51-61